SYNTHESIS OPTIMIZATION AND CHARACTERIZATION OF MOLECULARLY IMPRINTED POLYMER OF PROBENECID IN VARIOUS SOLVENTS - Stephanie, Christie
Probenecid is a uricosuric agent included in World Anti-Doping Agency (WADA)’s Prohibited List, categorized as diuretics and masking agents. Probenecid has the ability to cause substantial reduction effect towards endogen and synthetic androgenic steroid excretion. The Minimum Required Performance Levels (MRPL) of probenecid is 200 ng/mL as whole and free probenecid. As the percentage of excreted probenecid in whole and free form is very small, there is a necessity for the development of a sample preparation method that allows analyte selective separation and sample clean-up (probenecid preconcentration). One of the potential choices is the development of a Molecularly Imprinted Polymer (MIP) of probenecid. This study aims to optimize the synthesis and characterization of MIP of probenecid in various solvents. In this experiment, the probenecid-imprinted polymer was synthesized with acrylamide as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the cross-linker, and azoisobutyronitrile (AIBN) as the initiator of the polymerization. In the synthesis step, the probenecidacrylamide ratio was optimized at the ratios of 1:4, 1:5, and 1:6 in acetone, followed by the optimization of the porogenic solvent used in the synthesis, using tetrahydrofuran (THF), acetone, acetonitrile, and chloroform. Based on visual inspection and characterization using an infrared spectrometer (FTIR), probenecid-imprinted polymers were successfully synthesized with the composition 1:6 ratio producing the most excellent MIP which the infrared spectra showed numerous probenecid peaks which were not detected in Non-Imprinted Polymer (NIP) spectra and gave a different spectra compared to the one of the physically mixed NIP and probenecid. On the extraction step, acetonitrile also successfully extracted probenecid from the synthesized MIP, proved through the infrared spectra of the MIP before and after extraction, also the absorbance of the extraction solution measurement using spectrophotometer UV-Visible. Based on the batch binding analysis result, MIP with probenecid-acrylamide ratio at 1:6 using acetone as the porogenic solvent had the best binding capacity (Q = 3,888) and MIP resulted from THF had the best imprinting factor value (IF = 2). MIPs synthesized in acetone, acetonitrile, and THF had imprinting value bigger than one, which proved the recognition sites in the MIP was successfully formed and the synthesized MIP can selectively separate the analyte better than the NIP.